Pengaruh Sosialisasi Perpajakan, Modernisasi Sistem Dan Insentif Pajak Terhadap Kepatuhan Wajib Pajak Badan - Safitri, Della Ayu; Syafitri, Lili; Meiriasari, Vhika (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study was conducted to determine whether tax socialization, system modernization, and tax incentives affect corporate taxpayer compliance at KPP Pratama Ilir Barat Palembang City. This study involved 100 respondents selected through purposive sampling technique, which is a sample selection method based on certain criteria relevant to the research objectives. Data analysis uses Partial Least Square Structural Equation Modeling (PLS-SEM), which is assisted by SmartPLS 4.0 software to process and analyze data more accurately. The test results that have been carried out prove that tax socialization has a positive and significant effect on corporate taxpayer compliance with a sample average value of 0.208. System modernization also has a positive and significant effect on corporate taxpayer compliance with a sample average value of 0.333. Meanwhile, tax incentives show a positive and significant effect on corporate taxpayer compliance with an average value of 0.375. The research is expected to support the government's plan to increase corporate taxpayer compliance by optimizing a comprehensive socialization program, accelerating the modernization of the tax system, and increasing the effectiveness of providing targeted and sustainable tax incentives to encourage active participation of taxpayers.